BREVE ANÁLISE DA INSTRUÇÃO PROBATÓRIA DO JUIZ CRIMINAL BRASILEIRO SOB A ÉGIDE DO SISTEMA ACUSATÓRIO - Freitas, Ana Luiza Policani (Revista da Seção Judiciária do Rio de Janeiro - Auditorium; v. 22 n. 43 (2018): Direitos Humanos em Perspectiva, 2018)
This work brings an analysis  of the Brazilian Criminal Judge in the course of  evidential instruction and it’s instructor action under the accusatory criminal system with constitutional understanding adopted in the country after the promulgation of the civil constitution of 1988. The Accusatory,  Inquisitorial and mixed Criminal Systems will be demonstrated as the doctrinal controversies related to their core with basis on evidence management. Following, the subject of evidence in the accusatory system will be addressed, as its conception under the rules in this system, the roles given to the magistrate during the evidence production phase and the problems arisen from allowing the judge to produce them and the principles related to evidence management. It is important to mention that it is the Prosecutor’s Office role to gather evidence and not the magistrate’s, since the defense has no “Equality of arms” when it comes to gathering evidence. However, the Brazilian Magna Carta, which includes such system, must be respected together with the criminal law procedures under the judge’s tutelage due its supremacy in the hierarchy of laws, safekeeping the defendant’s fundamental rights.